The Selection of Migrants and Returnees : Evidence from Romania and Implications - Ambrosini, J. William (World Bank, Washington, DC, 2017)
This paper uses micro data from the Demographic National Survey and the Census in Romania (2002-2003) and in Countries that have received large number of Romanian immigrants over the period 1990-2000 (US, Austria and Spain) to identify the wage earning ability (skills) of migrants and returnees relative to non-migrants. This determines what is called 'selection'. Using observable characteristics (education, age, gender and family status) that affect wage earning abilities of non-migrant, migrants to specific countries and returnees the authors can construct measures of average selection across skills for each skill group. Also, by observing the actual wages of these groups in Romania, US, Austria and Spain the author can measure the average and the skills-specific premium for migrating and for returning. As the three receiving countries differ in their skill compensation structure we can test the hypothesis that migration to a country is larger for those groups that receive higher migration premium. The authors find strong support for the idea that migrants in different skill groups move depending on the premium that they will get in the receiving country. Similarly the authors find evidence of a premium to returnee that is increasing in their skills, which drives positive selection of returnees. As migration and return seem consistent with optimal utility-maximizing choices of individuals the authors use a model of education, migration and return to predict the effects of increasing international mobility on skill and wage of Romanians. The authors find average positive long-run effect on average skills and wages in Romania from relaxing migration constraint.